The Effect of Organizational Justice and Service Quality on Customer Perceived Value among University Students: : Controlling the Effect of Demographic Variables (Age, Gender, Social-Economic Status, and GPA) - Dodi Ilham Mustaring; Ahmad Syarief Iskandar (International Journal of Educational Administration, Management, and Leadership, 2022)
This study investigates the effect of a university's organizational justice and service quality on the students' perceived value of higher education institutions. Many studies have investigated the importance of customer perceived value in business. Several predictors have been identified, such as service quality and fairness in service. However, business and public sector services have distinct characteristics that define each sector. Considering the importance of education services and the role of higher education institutions, this study explored the contribution of organizational justice and service quality to students' perceived value. There were 517 students from higher education institutions who participated in the study. They were recruited through online advertisements, and the survey was completed online. The results confirmed the contribution of organizational justice and service quality to students' perceived value. The results were consistent after controlling the effect of other demographic variables (e.g., gender). This study suggested that organizational justice and service quality should be fostered in Indonesian higher education institutions. Organizational justice in higher education can instil a sense of proper educational management while service quality assures the university's high standard of services. Like other customers in business, students in higher education also expect value for their education. However, if they find injustice and poor services at their university, they will be more likely to perceive low value. This study has confirmed the application of organizational justice and quality service theory in higher education services.